A new fungicolous species of Hydropisphaera (Bionectriaceae, Hypocreales) from central China - Zeng, Zhao-Qing; Zhuang, Wen-Ying (Phytotaxa, 2016)
A new fungicolous species, Hydropisphaera spinulosa, is described and illustrated based on a collection from central China. It is characterized by non-stromatic perithecia that are solitary to gregarious, globose to subglobose, and becoming cupulate upon drying. The asci are clavate, without an apical ring, and with ascospores that are ellipsoidal to fusiform, uniseptate, and with a spinulose surface. The asexual state is acremonium-like. Comparisons are made between the new species and morphologically similar taxa. Its taxonomic position in Hydropisphaera is confirmed by sequence analysis of the large subunit of the nuclear ribosomal DNA.